Grupo operativo no hospital-dia: uma alternativa de atendimento em saúde mental - Oliveira, Francisca Bezerra de (1991)
The present study has an objective of attention the therapeutical activiy of operative group to psychotic clients assistefi by regime of Day Hospital. The group therapeutical process is described from pratical intervention in the mentioned activity, the methodological referencial being the qualitative approach “research-action”, highlighting its most significant moments with emphasis on the participants speechds. Followmg that, there’s a "cut" of the social part icilpants representations in contrast with the reality surrourding them, through the most frequent subjects appearing on the section. The conclusion i s that this modality can be an alternative in mental health assistance, since the participants develop active/critical role during the group procese, as well as there is a gradual and mutual learning between clients and technicians related to the proposed activity.